An investigation into possible interactions in the vestibular system and the cochlea during electrical stimulation - Lanthaler, David; Griessner, Andreas; Steixner, Viktor; Corre, Julie; Ranieri, Maurizio; Cavuscens, Samuel; Grouvel, Gautier; Guinand, Nils; Zierhofer, Clemens M.; Fornos, Angélica Pérez (Frontiers in Neuroscience, 2025)
IntroductionThe vestibular system is crucial for balance, spatial orientation, and gaze stabilization. Bilateral vestibulopathy (BV) severely impairs these functions, often co-occurring with severe to profound hearing loss. Combined cochleo-vestibular implants have the potential to rehabilitate these dual sensory impairments. These investigational devices have been used by a small group of subjects with both severe hearing loss and bilateral vestibular loss. When electrically stimulating both the cochlea and the vestibular system, understanding electrical interactions is essential for the successful fitting and operation of these combined implants. The aim of this study was to investigate the influence of vestibular pulses on cochlear and vestibular perception, and vice versa.MethodsIn our study, we conducted experiments on three recipients of cochleo-vestibular implants, measuring auditory and vestibular perceptual thresholds under controlled conditions. The study examined three interaction paradigms: vestibulo-cochlear, cochleo-vestibular, and vestibulo-vestibular interactions. A staircase procedure was used to determine perceptual thresholds to evaluate the impact of concurrent stimulation on each sensory system.ResultsThe results showed subject-specific interactions, with significant threshold shifts observed in some cases due to the concurrent stimulation of cochlear and vestibular electrodes. Vestibulo-vestibular interactions consistently led to increased thresholds, indicating electrical interference within the vestibular system. In contrast, vestibulo-cochlear and cochleo-vestibular interactions demonstrated more variable effects, with threshold shifts observed in two of the three subjects.DiscussionThese findings suggest that the dual stimulation of the cochlear and vestibular systems must be carefully managed to avoid compromising auditory or vestibular performance. In future research, focusing on larger cohorts could help to better understand the variability in subject responses. In addition, exploring functional effects of these interactions on subjects’ performances during normal implant use would complement the threshold measurements of the current study.